Quality management system and practices - Ng, Kim-Soon (IntechOpen, 2012)
Quality is a perceptual, conditional and somewhat subjective attribute of a product or service. Its meaning in business has developed over time. It has been understood differently and interpreted differently by different people. A business will benefit most through focusing on the key processes that provide their customers with products and services. Producers may measure the conformance quality, or degree to which the product or service was made according to the required specification. Customers on the other hand, may focus on the quality specification of a product or service, or compared it with those that are available in the marketplace. In a modern global marketplace, quality is a key competency which companies derive competitive advantage. Achieving quality is fundamental to competition in business in propelling business into new heights. Many quality management philosophies, methodologies, concepts and practices were created by quality gurus to manage quality of product and service in an organization. These practices have evolved over time to create sustainable sources of competitive advantage. New challenges faced by managers are addressed to improve organization’s performance and future competition. In the total quality management form, it is a structured management system adopted at every management levels that focused on ongoing effort to provide product or service. Its integration with the business plan of the organization can exact positive influence on customer satisfaction and organizational performance. This chapter dealt with what is quality and TQM, cost of quality, linking quality management system to organizational performance, its impact on organizations and approaches of implementing TQM and the quality journey.